2022
DOI: 10.1038/s41433-022-02070-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of different keratoconus detection indices of pentacam in paediatric eyes

Abstract: Objective No diagnostic gold standard for keratoconus in children and adolescents exists. Our objective was investigating the diagnostic accuracy of various indices for keratoconus (KC) detection in paediatric eyes. Methods All retrievable data of significance from 432 normal right paediatric eyes and 48 eyes of paediatric KC and forme fruste KC (FFKC), imaged by use of a rotating Scheimpflug camera (Oculyzer II, Pentacam HR) between December 2013 and Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
1
8
1
Order By: Relevance
“…The normal group comprised normal eyes of patients evaluated for refractive surgery. Rotating Scheimpflug imaging system Nil Hashem et al, 2022 18 Egypt Out-patients 480 13.5, 15.3 The study group comprised normal paediatric right eyes while the study group comprised eyes of paediatric keratoconus Rotating Scheimpflug Camera (Oculyzer II, Pentacam HR) The Science and Innovation Funding in cooperation with The Egyptian Knowledge Bank Bae et al, 2014 19 South Korea Out-patients 48 28, 25.08 Patients who had advanced KC in one eye and a normal fellow eye were considered unilateral KC. The normal control patients were candidates for refractive surgery with clinically normal corneas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The normal group comprised normal eyes of patients evaluated for refractive surgery. Rotating Scheimpflug imaging system Nil Hashem et al, 2022 18 Egypt Out-patients 480 13.5, 15.3 The study group comprised normal paediatric right eyes while the study group comprised eyes of paediatric keratoconus Rotating Scheimpflug Camera (Oculyzer II, Pentacam HR) The Science and Innovation Funding in cooperation with The Egyptian Knowledge Bank Bae et al, 2014 19 South Korea Out-patients 48 28, 25.08 Patients who had advanced KC in one eye and a normal fellow eye were considered unilateral KC. The normal control patients were candidates for refractive surgery with clinically normal corneas.…”
Section: Resultsmentioning
confidence: 99%
“…Figure18 Bubble plots of meta-regression for the effect of publication year on K1, K2, Kmax and CCT (A-D respectively.…”
mentioning
confidence: 99%
“…Comparisons between the diabetic and non-diabetic groups showed that only PPIavg and PPImax were statistically higher in the diabetic versus non-diabetic subjects. Tomography-derived pachymetric indices such as PPI values are better for the differential diagnosis of normal from abnormal corneas compared to single-point corneal thickness measurements [ 16 , 17 ]. Several studies compared central corneal thickness between the diabetic and non-diabetic groups [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…As KC in young patients is reported to be more likely to progress than in adults, the sensitivity index and cutoff values of parameters in pediatric patients is different than in adult patients. (Hashem et al, 2022;Neustein and Lenhart, 2022). The machine learning analysis, analyzing a large number of variables, found that the Pentacam is one of the most common techniques in clinical application, as the uniqueness of this device is that it includes tomographic data, topometric data, pachymetry, elevation data, and combined data.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective observational study conducted in Egypt reported the eight most useful Pentacam indices in identifying 48 eyes of pediatric KC and SKC. (Hashem et al, 2022). Furthermore, the corneal biomechanics, which are thought to be the initiators of the disease even before notable changes in corneal morphology, were not evaluated in the above study.…”
Section: Introductionmentioning
confidence: 99%